A high spectral efficiency and load-aware metric for path selection in IEEE 802.16j multi-hop relay networks - Kuei-Ping Shih; Sheng-Shih Wang; Chan-Ying Lien (2009 IEEE Symposium on Computers and Communications, 2009)
In the IEEE 802.16j multi-hop relay (MR) network, the design of an effective path selection scheme is an important issue for throughput gain and overhead reduction. This paper proposes a new metric, called SEL, to evaluate the possible relay paths and thereby determine the appropriate one among these paths. SEL mainly considers both link spectral efficiency and link load, and based on SEL, a comprising function is developed to formulate the path cost to select the appropriate relay path. As confirmed by the performance evaluation, the proposed path selection scheme with SEL consideration significantly outperforms the existing path selection schemes in network throughput and map overhead.